Comparison of IAS 39 and IFRS 9: The Analysis of Replacement - Mojca Gornjak (International Journal of Management, Knowledge and Learning, 2017)
The financial crisis had an impact on international financial reporting standards. The International Accounting Standards Board (IASB) prepared a new standard for financial instruments. The replacement changes the view to accounting data in financial statements and changes the view to data in organizations, especially banks, and financial institutions. Historical prices are replaced with expectation in the future, which is not anymore a decision of the managers but has its basis on business operations.